Potential health and economic impact of achieving Kenya’s overweight and obesity reduction target: a modelling study - J Lennert Veerman; Leopold Ndemnge Aminde; Mary Njeri Wanjau (BMJ Public Health)
Introduction Kenya has adopted the WHO target of halting the rise of overweight, including obesity, by 2025. This paper assesses the potential impact of achieving the set target on health, healthcare cost and productivity.Methods We used a proportional multistate life table model (Kenya Obesity Model) to simulate the 2019 population of Kenya over their lifetime. We compared a scenario in which body mass index (BMI) distributions stabilise in 2025 against one whose BMI distributions stabilise in 2044, and quantified changes in disease-specific health outcomes, healthcare costs and productivity. We searched the literature to identify the best estimates of the total and disease-specific healthcare costs in Kenya. We used the Human Capital Approach to estimate productivity gains.Results If BMI distributions stabilised in 2025, an estimated 6.8 million health-adjusted life years (HALYs) (95% uncertainty interval (UI) 5.8–7.9 million) would be saved over the lifetime of the 2019 Kenyan population (135 HALYs per 1000 persons). A total of US$755 million in body mass-related healthcare costs could be saved by 2044 (US$15 per capita). For context, this equates to 16% of Kenya’s annual healthcare expenditure. Over the lifetime, ~US$3 billion healthcare costs could be saved (US$62 per capita). By 2044, the total productivity gain resulting from a reduction in high BMI-related mortality and morbidity (combined) was ~US$5.8 billion (~US$237 per capita).Conclusion Achieving Kenya’s overweight and obesity reduction target could improve health outcomes and also yield substantial healthcare cost savings and productivity gains.